Efecto de inhibidores de nitrificación y poda en el cultivo de arándano (Vaccinium corymbosum L.) var. Biloxi bajo criterios edáficos y calidad de fruto en condiciones de campo, en el sector La Argelia - Granda Morocho, Juan Fernando (2024)
Blueberry is a globally significant crop due to its high demand attributed to its perceived health benefits. Ecuador has recently implemented cultivation of this fruit by producers, with limited production in specific locations. Consequently, there is limited knowledge regarding nitrogen fertilization and agronomic techniques such as pruning. The objective of this research was to evaluate the fruit quality of blueberry (Vaccinium corymbosum L.) var Biloxi subjected to two pruning intensities and two types of fertilization, focusing on morphological and physiological plant variables, as well as soil pH and electrical conductivity. The trial was conducted at the Quinta Experimental Docente "La Argelia" in the province of Loja, using a split-plot experimental design with four treatments and six repetitions. The main plot represented the pruning factor (with pruning and without pruning), and the subplot represented the fertilization factor (ammonium sulfate and ammonium sulfate with the nitrification inhibitor). Results indicated that the interaction between pruning and nitrogen fertilization had no significant effect on variables such as leaf area, leaf area index, crown diameter, plant coverage, and stomatal conductance. A significant increase in chlorophyll concentration, as measured by SPAD, was observed in treatments with ammonium sulfate combined with the nitrification inhibitor DMPP, regardless of the pruning factor. Soil pH and electrical conductivity (EC) were altered, although not significantly, by fertilization, leading to increased soil acidity. Regarding variables related to the second objective of fruit quality, pruning had a considerable influence on equatorial and polar diameters. Pruned plants exhibited an average equatorial diameter of 16.2 mm and a polar diameter of 12.5 mm, while the non-pruned treatment showed an equatorial diameter of 14.9 mm and a polar diameter of 11.4 mm. No significant differences were found in fruit firmness, with all treatments falling within the same firmness range. Soluble solids in pruned treatments averaged 13%, whereas the non-pruned treatment yielded an average of 11%. Pruned plants produced fruits with an average weight of 1.98 g, while non-pruned plants had an average weight of 1.49 g. Overall, fruit yield estimates were similar across all treatments, indicating that pruning did not significantly impact yield.